A tight control treatment strategy aiming for remission in early rheumatoid arthritis is more effective than usual care treatment in daily clinical practice: a study of two cohorts in the Dutch Rheumatoid Arthritis Monitoring registry. Issue 6 (30th December 2011) - Schipper, Lydia G; Vermeer, Marloes; Kuper, Hillechiena H; Hoekstra, Monique O; Haagsma, Cees J; Broeder, Alfons A Den; Riel, Piet van; Fransen, Jaap; van de Laar, Mart AFJ
Abstract : There is strong evidence from clinical trials that a 'treat to target' strategy is effective in reaching remission in rheumatoid arthritis (RA). However, the question is whether these results can be translated into daily clinical practice and clinical remission is a reachable target indeed. Objective: The study aims to investigate whether in early RA a treatment strategy aiming at Disease Activity Score (DAS) 28 <2.6 is more effective than 'usual care' treatment for reaching clinical remission after 1 year. Methods: Two early RA inception cohorts from two different regions including patients who fulfilled the American College of Rheumatology criteria for RA were compared. Patients in the tight-control cohort (n=126) were treated according to a DAS28-driven step-up treatment strategy starting with methotrexate, addition of sulphasalazine (SSZ) and exchange of SSZ by anti-tumour necrosis factor in case of failure. Patients in the usual-care cohort (n=126) were treated with methotrexate or SSZ, without DAS28-guided treatment decisions. The primary outcome was the percentage remission (DAS28<2.6) at 1 year. Time to first remission and change in DAS28 were secondary outcomes. Results: After 1 year, 55% of tight-control patients had a DAS28<2.6 versus 30% of usual care patients (OR 3.1, 95% CI 1.8 to 5.2). The median time to first remission was 25 weeks for tight control and more than 52 weeks for usual care (p<0.0001). The DAS28 decreased with −2.5 in tight control and −1.5 in usual care (p<0.0001). Conclusion: In early RA, a tight control treatment strategy aiming for remission leads to more rapid DAS28 remission and higher percentages of remission after 1 year than does a usual care treatment.